THE FEMALE VOICE OF JUSTICE IN ARATUS' PHAENOMENA*. (25th March 2015) - Unknown
Abstract : Aratus' striking mythical digression (96–136) in the Phaenomena on the constellation of the Maiden (Παρθένος), whom he identifies with the virginal Justice (Δίκη), stands out against the preceding technical description of star groups. The passage has unsurprisingly received the frequent notice of critics, with particular attention paid to the episode's relation to and refashioning of the Myth of Ages in Hesiod's Works and Days 106–201: one tale that circulates among men, so the narrator informs us (λόγος γε μὲν ἐντρέχει ἄλλος | ἀνθρώποις, 100–1), has the constellation qua Dike live among men and women in a Golden Age (101–14), withdraw to the mountains but still visit humans in a Silver Age (115–29), and then withdraw permanently to the sky (where, however, she is still visible) in a Bronze Age (129–36).